Ayurvedic Management of Drug Resistant Obsessive Compulsive Disorder - Vipin, Sharika; Jithesh M (International Research Journal of Ayurveda & Yoga, 2024)
Obsessive compulsive disorder (OCD) is a debilitating neuropsychiatric disorder with a lifetime prevalence of 2 to 3 percent. Selective serotonin reuptake inhibitors (SSRIs) and Clomipramine are the established pharmacologic first-line treatments for OCD, and Exposure Response Prevention (ERP) is recommended as the first-line behavioral intervention, with Cognitive Behavioral Therapy (CBT) as an alternative. About 40-60% of patients show no or just partial symptom improvement from drug treatment, and long-term management results in significant adverse effects. Drug-resistant OCD is defined as individuals who have persisting symptoms after being exposed to at least two trials (6 months) of SSRIs. Psychiatric illness is dealt with as one of the 8 specialties of Ayurveda named Bhutavidya. According to the presentation and severity of symptoms, OCD can be diagnosed as Unmada. According to the evolved dosha status and severity of the symptoms, the management can be done with sodhana, samana, and rasayana chikitsa. Studies suggest that the add-on effect of Yoga can also be beneficial in OCD. A 40-year-old female presented with recurrent, persistent thoughts about contamination followed by increased cleaning rituals such as excessive hand washing, increased time taken for bathing, and washing clothes. This condition was diagnosed as OCD, and she had been on SSRIs for more than 3 years, but no relief in symptoms was found. She underwent various treatments, and the total duration of intervention was 45 days. The Yale-Brown Obsessive Compulsive Disorder (Y-BOCS) score was 38 upon admission, which reduced to 19 after intervention.